MODELS OF PARTNERSHIPS AND ORGANISATIONAL FORMS IN SHORT FOOD SUPPLY CHAINS IN THE SLOVENIAN MOUNTAINS - Borec, Andreja; Prišenk, Jernej (Economics of Agriculture, 2013)
An important condition for the efficient production and marketing of local food products in mountainous regions is broadly recognised in cooperation between different partners along the food supply chain. Cooperation between different actors, organisational forms and sectors is especially important in mountains and less favoured areas characterised by limited conditions for agriculture and, consequently, where few raw materials are produced. This article presents a study aimed at identifying the positive effects of cooperation between actors, organisational forms and sectors in the production and marketing system of local food products in the Slovenian mountains. Ten products were included in the study. The results indicate that the presence of the private sector both in the production and marketing system is an important condition for creating a successful and solid food supply chain.